Ermittlung möglicher Fusionseffekte im ÖPNV. Eine Effizienzanalyse für Nordrhein-Westfalen. - Hirschhausen, Christian von; Cullmann, Astrid; Walter, Matthias (Deutscher Verkehrs-Verl., 2008)
Fusionen steigern Effizienz. Zur Schaffung eines zukunftsfähigen und effizienteren ÖPNV sind die Fusionen von Straßen- und Stadtbahnbetreibern mit benachbarten Busunternehmen ein probates Mittel. Dies belegt eine am Lehrstuhl für Energiewirtschaft und Public Sector Management der Technischen Universität Dresden durchgeführte wissenschaftliche Analyse, mit der die Effizienzpotenziale von Fusionen abgeschätzt werden können. Damit erhöht sich der Druck auf Politik und Unternehmen, Fusionen zu unterstützen und weiter voranzutreiben.

The article summarizes recent research in efficiency analysis of multi-output companies in local public transport. We analyze the potential gains from mergers in Germany's most densely populated area, North Rhine Westphalia. We first give an overview of current market structure challenges, mainly tenders and mergers, in Germany's local public transport. We then present our results which support the ongoing efforts to merge companies operating on a tram or light railway network with connecting lines. Mergers of big multi-output companies with neighbouring pure bus operators seem also beneficial and hence should be facilitated by policymakers. Our decomposition of merger gains underpins the current inefficiency inherent in the market, which is mostly due to labour inefficiency. The significant real merger gains can in particular be assigned to synergy gains.
Potential gains from mergers in German local public transport.
Keywords: Öffentlicher Verkehr; ÖPNV; Schienenpersonenverkehr; Busverkehr; Verkehrsunternehmen; Leistungsfähigkeit; Ausschreibung; Wettbewerb; Kooperation; Verkehrsverbund; Fusion; SPNV; Verkehrsdienstleistung; Qualitätsverbesserung; Synergieeffekt